Cocoa irrigation in southern Nigeria: A Technical Report of the IITA irrigated cocoa farm - Oke, Adebayo; Hauser, Stefan; Schmitter, Petra S.; Mabhaudhi, Tafadzwanashe (International Institute of Tropical Agriculture, 2023)
Cocoa production is a major export crop in West African countries such as Liberia, Cote d’Ivoire, Ghana, Togo, and Nigeria. These countries collectively contribute to 70% of global cocoa production. Cote d’Ivoire, Ghana, Nigeria, Liberia, and Togo are leading economies and significant hubs for cocoa production. Cocoa cultivation in West Africa primarily relies on rainfall, with approximately six million hectares of land dedicated to cocoa production. climate change is exacerbating the challenge of pests and diseases in cocoa production, with common issues including black pod and cocoa swollen virus. Aging cocoa farms experience reduced productivity, leading to their replacement with arable crop production. Moreover, certain major cocoa-producing areas are becoming marginal due to rising temperatures and reduced rainfall. In Ghana, these areas, called Transition Zones, increasingly require climate-smart adaptations and interventions. This is responsible for the growing interest in cocoa irrigation in West Africa. The International Institute of Tropical Agriculture (IITA) has undertaken significant research initiatives in cocoa development across West Africa. The research efforts primarily aim to increase cocoa productivity. Cocoa research stations in Nigeria, like other stations, were equipped with drip irrigation facilities. However, the performance of the irrigation became inefficient after some years of operation. Issues experienced in the field include instances of die-back of cocoa trees, loss in yield, inadequate irrigation in the dry season, poor irrigation distribution across the field, and inadequacy of water supply for irrigation.